2020
DOI: 10.1111/1756-185x.13935
|View full text |Cite
|
Sign up to set email alerts
|

A discovery of screening markers for rheumatoid arthritis by liquid chromatography mass spectrometry: A metabolomic approach

Abstract: Rheumatoid arthritis (RA) is a chronic autoimmune disease in which the synovial joints are inflamed and swollen and the bone is eroded. About 1% of the adult population worldwide suffers from RA 2 and it is more common in women than in men. The discovery of biomarkers that can lead to earlier diagnosis and possible prevention will aid in reducing joint damage and improving disease prognosis. 3 However, rheumatoid factor (RF), currently known as a representative diagnostic marker for RA, is easily detected in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…However, while succinate was detected in the synovial fluid in a separate comparison of several inflammatory and non-inflammatory arthritis types, no metabolic distinction was found between patient groups in this study ( 112 ). Metabolomic studies of plasma and serum found no significant differences in succinate levels between RA patients and controls ( 91 , 113 115 ), or between RA patient groups with differing disease activity ( 114 ), meaning that succinate levels are unlikely to be a useful clinical biomarker of disease. It is unclear whether these different results represent mechanistic differences in disease processes between the circulation and synovium, or if the power of the studies was insufficient to detect differences in this metabolite in serum samples.…”
Section: Tca Cycle Metabolitesmentioning
confidence: 98%
“…However, while succinate was detected in the synovial fluid in a separate comparison of several inflammatory and non-inflammatory arthritis types, no metabolic distinction was found between patient groups in this study ( 112 ). Metabolomic studies of plasma and serum found no significant differences in succinate levels between RA patients and controls ( 91 , 113 115 ), or between RA patient groups with differing disease activity ( 114 ), meaning that succinate levels are unlikely to be a useful clinical biomarker of disease. It is unclear whether these different results represent mechanistic differences in disease processes between the circulation and synovium, or if the power of the studies was insufficient to detect differences in this metabolite in serum samples.…”
Section: Tca Cycle Metabolitesmentioning
confidence: 98%
“…Of note, these metabolites were signi cantly reduced in collagen-induced arthritis mice compared to controls 9 . We also identi ed DHEA sulfate as the metabolite with the lowest RA/HC ratio, in alignment with the literature 10 .…”
Section: Discussionmentioning
confidence: 55%
“…At the same time, this inflammatory reaction will promote each other with phosphoethanolamine (PE) resulting in the increase of PE [ 20 ], and anandamide is the metabolite of PE [ 21 ], but our study also found different results. Androsterone sulfate and dehydroepiandrosterone (DHEA) sulfate may be related to the development of inflammation and immunoregulatory activity [ 22 ], but our study shows the opposite trend to other inflammatory diseases. Some studies have found that when the body is in the state of oxidative stress, the body will inhibit the synthesis of coenzyme A in cells [ 23 ].…”
Section: Discussionmentioning
confidence: 66%